New view on the age-specificity of pig Cryptosporidium by species-specific primers for distinguishing Cryptosporidium suis and Cryptosporidium pig genotype II - Jeníková, Martina; Němejc, Karel; Sak, Bohumil; Květoňová, Dana; Kváč, Martin (Veterinary parasitology, 2011)
Two species of Cryptosporidium are commonly identified in pigs: Cryptosporidium suis and Cryptosporidium pig genotype II. Detection of Cryptosporidium spp. is routinely based on molecular methods such as polymerase chain reaction (PCR) and subsequent restriction fragment length polymorphism (RFLP) or gene sequencing. However, most of these methods are hampered by low sensitivity to mixed infections. As a solution of this problem, novel species-specific primers were designed and tested in the present study. Sensitivity of our primers was identical to genus-specific primers, but more (1:48) mixed infections were detected using these species-specific primers on 477 DNA samples originating from naturally infected pigs of different age categories. Our results show differences in age-dependent susceptibility of pigs to the infection. Whereas C. suis was found in all tested categories of pigs (1-12 week of age and sows), Cryptosporidium pig genotype II was recorded only in animals older than 6 week of age. Usage of species-specific primers could help to better the understanding of epidemiology of pig specific Cryptosporidium spp. and its occurrence, which, on the basis of our results, is underestimated.
Keywords: prasata; Cryptosporidiosis; Swine Diseases; Swine; Age Distribution; Cryptosporidium; druhová specificita; genotyp; věkové rozložení; RNA ribozomální 18S; Animals; Species Specificity; Genotype; nemoci prasat; zvířata; kryptosporidióza; RNA, Ribosomal, 18S